2020
DOI: 10.1007/s00535-020-01682-y
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of glycaemia following acute pancreatitis: a prospective longitudinal cohort study with 24 months follow-up

Abstract: Background New-onset diabetes is the most common sequela of acute pancreatitis (AP). Yet, prospective changes in glycaemia over time have never been investigated comprehensively in this study population. The primary aim was to determine the cumulative incidence of new-onset prediabetes and new-onset diabetes after AP over 24 months of follow-up in a prospective cohort study. The secondary aim was to identify trajectories of glycaemia during follow-up and their predictors at the time of hospitalisation. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 55 publications
0
47
0
Order By: Relevance
“…Due to confusion with type 2 diabetes mellitus (T2DM) ( Petrov, 2017 ), it has been underestimated in clinical practice for a long time. The incidence of DEP varies with geographical distribution and etiology ( Ewald and Hardt, 2013 ; Pendharkar et al, 2017 ; Woodmansey et al, 2017 ; Bharmal et al, 2020a ), with estimated true prevalence ranging from 1 to 9% of all diabetic patients ( Hart et al, 2016 ). It has been noted that compared to other DM patients, the DEP patients present additional symptoms related to pancreatic disease, including decreased glucagon and somatostatin, pancreatic exocrine insufficiency (PEI), malabsorption of nutrients and micronutrients, severe and painful gastrointestinal symptoms, and nutritional deficiencies ( Wynne et al, 2019 ).…”
Section: Introduction: Clinical Features Of Depmentioning
confidence: 99%
“…Due to confusion with type 2 diabetes mellitus (T2DM) ( Petrov, 2017 ), it has been underestimated in clinical practice for a long time. The incidence of DEP varies with geographical distribution and etiology ( Ewald and Hardt, 2013 ; Pendharkar et al, 2017 ; Woodmansey et al, 2017 ; Bharmal et al, 2020a ), with estimated true prevalence ranging from 1 to 9% of all diabetic patients ( Hart et al, 2016 ). It has been noted that compared to other DM patients, the DEP patients present additional symptoms related to pancreatic disease, including decreased glucagon and somatostatin, pancreatic exocrine insufficiency (PEI), malabsorption of nutrients and micronutrients, severe and painful gastrointestinal symptoms, and nutritional deficiencies ( Wynne et al, 2019 ).…”
Section: Introduction: Clinical Features Of Depmentioning
confidence: 99%
“…Initially thought to be mainly a self-resolving disease, emerging evidence has shown that individuals after AP often develop metabolic derangements after hospital discharge-in particular, new-onset prediabetes or diabetes after AP (NODAP) [1][2][3][4][5][6]. For example, a 2020 prospective longitudinal cohort study (as part of the LACERTA project) demonstrated that 43% of non-diabetic patients with AP developed NODAP within two years after hospital discharge [7]. There is a growing appreciation that NODAP is different from type 2 prediabetes or diabetes mellitus (T2DM).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the development of DEP is known to be influenced by a range of factors. In addition to the conventional risk factors for diabetes (e.g., central obesity) ( 29 , 30 ), recurrent episodes of AP—a pancreas-specific risk factor for DEP—( 31 ) might have differentially contributed to the incidence of DEP during the observation period.…”
Section: Discussionmentioning
confidence: 99%